PLANFOR: política compensatória para a inclusão na informalidade? - Sales, Francisco José Lima (2006)
Study about the national politics on the professional education, under responsibility of the brazilian Work Department in 1990 years. Purposes to apprehend the results of the actions of the professional education in a basic level, offered by the National Plan of the worker qualification ( PLANFOR ), as well as the effects on the assisted exits, starting from the experience appreciated on the Plan of Qualification developed in the state of Maranhão between 1996 to 2000. It adopts a theoretical-methodological conception by an ontological nature, if being worth of categories as the one of totality and of mediation that together, makes possible the apprehension of a dialectical movement that happens among the analysis object, the professional education politics in a basic level, performed by PLANFOR and your context, the underdevelop and heterogeneous Brazilian capitalism and the consequent job market generalized precarious and informal, making possible that the reality investigated become to understood rationally. This paper uses the indirect documentation technique, instruments of the bibliographical research and documental research. This study is based on those that aren´t part of PLANFOR, qualified by professional education courses in basic level,they didn't get to be inserts at the formal job market, just occupying precarious occupations in the informal job market. Aims to presents and discusses the productive process and your restructuring globally in progress. It focuses at the impacts on the workers, the precariousness of the work that appears like a new phenomenon calls new informality. Talks about the particularity process of productive restructuring assumed in Brazil highlights, showing that the informality, was always a structural phenomenon in the country. Discusses about the professional qualification in the contemporary capitalism, specifying some of your theses. Shows in a historical view the process of appearance of the employment notions and competence, and the influence that it exercised on the reforms of the basic and professional education, as well as the implications of both in the politics of professional education in the country. Rescues the process of creation of PLANFOR, your official formulations and your organized bases, starting from the second half of the 1990 decade. Shows yet the continuos changes in the job market of Maranhão state, for after, starting from the reports expresses at the Plans of Qualification from the state, elaborated by the Group of Evaluation and Studies of the Poverty and the Politics addressed to the poverty from the Master degree Program in Public Politics, from the Federal University of Maranhão, analyzing the acting of PLANFOR in the State, your probable deficiencies, as results the changes verified in the conditions of occupation and the gains of the exits from the professional education courses in basic level